60.6k views
3 votes
Please help and thank you

Please help and thank you-example-1
User Sebrock
by
5.1k points

2 Answers

1 vote

Answer:


b_(1)=(2A)/(h)-b_(2)

Explanation:

Given:
A=(1)/(2)(b_(1) +b_(2))h

We need to completely isolate
b_(1) to solve.


A=(1)/(2)(b_(1) +b_(2))h


A=((1)/(2)b_(1) +(1)/(2) b_(2))h


A=(1)/(2)b_(1) h+(1)/(2)b_(2)h


-(1)/(2)b_(1)h+A=(1)/(2)b_(2)h


-(1)/(2)b_(1)h=-A+(1)/(2)b_(2)h


-(1)/(2)b_(1)=(-A)/(h)+(1)/(2)b_(2)

Finally, multiply both sides by -2 to completely isolate
b_(1).


b_(1)=(2A)/(h)-b_(2)

User Arun Gowda
by
4.7k points
4 votes

Answer:

The right option is D

Explanation:

See the image

Please help and thank you-example-1
User Olexii Muraviov
by
5.2k points